(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
This study was undertaken to identify the morphological andphysiological attributes related to drought tolerance in sorghum [Sorghumbicolor (L.) Moench]. Eight genotypes were tested in a pot experimentcarried out at Giessen, Germany. Drought conditions were imposed bywithholding watering of the plants when field water-holding capacity wasat 40% and 70%. The tested genotypes differed significantly in most ofthe measured traits. Grain yield under drought stress ranged from 28 to 61g/ plant, and relative yield ranged from 30% to 56% with an average of47%. Based on yield/plant, the genotypes Wad Ahmed (61g), SAR41(55g) and ICSR 91030 (54g) were the best under drought stressconditions; and based on relative yield, the best genotypes were SAR 41(56%), Wad Ahmed (55%), and Red Mugud (53%). The mean potassiumcontent was 18 mg/g, with a range of 14 mg/g (Red Mugud) to 22 mg/g(Arfa Gadamak). Significant differences were obtained for proteinpercentage of the dry matter under conditions of drought stress. Thevalues ranged from 14.1% (Red Mugud) to 16.7% (Tabat) with a mean of15.3%. Grain yield under drought stress was positively correlated with